A pilot trial of mobile, patient‐performed teledermoscopy. (1st April 2015) - Manahan, M.N.; Soyer, H.P.; Loescher, L.J.; Horsham, C.; Vagenas, D.; Whiteman, D.C.; Olsen, C.M.; Janda, M.
Summary: Background: Early detection by skin self‐examination (SSE) could improve outcomes for melanoma. Mobile teledermoscopy may aid this process. Objectives: To establish the clinical accuracy of SSE plus mobile teledermoscopy vs. clinical skin examination (CSE) and to test whether providing people with detailed SSE instructions improves accuracy. Methods: Men and women aged 50–64 years ( n = 58) performed SSE plus mobile teledermoscopy in their homes between May and November 2013 and were given technical instructions plus detailed SSE instructions (intervention) or technical instructions only (control). Within 3 months, they underwent a CSE. Outcome measures included (i) body sites examined, lesions photographed, and missed; (ii) sensitivity of SSE plus mobile teledermoscopy vs. in‐person CSE using either patients or lesions as denominator; and (iii) concordance of telediagnosis with CSE. Results: Overall 49 of 58 randomized participants completed the study, and submitted 309 lesions to the teledermatologist. Intervention‐group participants were more likely to submit lesions from their legs compared with controls ( P = 0·03), with no other differences. Eleven participants (22%) did not photograph 14 pigmented lesions that the dermatologist considered worthwhile photographing or monitoring. The sensitivity of SSE plus mobile teledermoscopy was 82% using the patient as denominator and 42% using the lesion as denominator. There was substantial agreement between telediagnosis and CSE (κ = 0·90), accounting for differential diagnoses. Conclusions: SSE plus mobile teledermoscopy is promising for surveillance of particular lesions even without detailed SSE instructions. However, in the format tested in this study, consumers may overlook lesions and send many nonpigmented lesions. This investigation demonstrates that high‐quality dermoscopic images can be taken by patients at home with high accuracy.